2017
DOI: 10.1007/978-1-4939-6993-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ADP-Ribose Acceptor Sites on In Vitro Modified Proteins by Liquid Chromatography–Tandem Mass Spectrometry

Abstract: Protein ADP-ribosylation is a covalent, reversible posttranslational modification (PTM) catalyzed by ADP-ribosyltransferases (ARTs). Proteins can be either mono- or poly-ADP-ribosylated under a variety of physiological and pathological conditions. To understand the functional contribution of protein ADP-ribosylation to normal and disease/stress states, modified protein and corresponding ADP-ribose acceptor site identification is crucial. Since ADP-ribosylation is a transient and relatively low abundant PTM, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…These samples were then processed for MS analysis as previously described [4,28,38]. The reactions were carried out as described above and stopped via addition of PJ34 to a final concentration of 10 lM.…”
Section: In Vitro Adp-ribosylation Assay With Recombinant Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…These samples were then processed for MS analysis as previously described [4,28,38]. The reactions were carried out as described above and stopped via addition of PJ34 to a final concentration of 10 lM.…”
Section: In Vitro Adp-ribosylation Assay With Recombinant Proteinsmentioning
confidence: 99%
“…Indeed, K152 and S154 of RPS3A were also identified as potential ADPr sites in the in vivo MS data presented above (Dataset EV3). To define the exact localization of the in vitro ADPr modifications on RPS3A, the ARTD1, HPF1, and RPS3A in vitro modification reactions were analyzed by MS using our ADPr-optimized HCD-PP-EThcD/HCD workflow [4,28]. As our group and others have clearly demonstrated that ETD or ETD-like fragmentation methods provide the most accurate data for localizing ADPr sites within a modified peptide [4,19], only the resulting EThcD spectra were used to define the ADPr-sites written on these proteins in vitro.…”
Section: Ms Analysis Of In Vitro Adp-ribosylation Assays Confirms Thamentioning
confidence: 99%
See 1 more Smart Citation
“…For detecting the specific ADP-ribosylated residues, quadruple tandem MS was indicated to detect ADP-ribosyl-Arg and Arg-ADP-ribosylated peptides to identify the specific arginine site of mono-ADP-ribosylation in the target protein (55,56). In recent years, numerous MS-based proteomics have been developed, such as macrodomain-linked immunosorbent assay to identify mono-ARTs (57) and liquid chromatography-high-resolution tandem MS to identify mono-ADP-ribose acceptor sites (58,59). Furthermore, there are other methods allowing for the identification of mono-ADP-ribosylation, such as a phosphoproteomics approach via the enzymatic product of phosphodiesterase-treated ADP-ribose (60) or an aminooxy alkyne probe for detecting mono-ADP-ribosylated proteins (61).…”
Section: Methods For Detecting Mono-adp-ribosylated Histonesmentioning
confidence: 99%
“…Leutert and coworkers generated tryptic peptides from PARG digested proteins using filter-aided sample preparation (FASP), enriched the resulting MARylated peptides using magnetic Ti 4+ -IMAC microspheres, and desalted the eluted peptides using C18-stage tips before LC-MS/MS analysis (Leutert et al, 2017). This protocol was only applied for the identification of in vitro ADPr, but it seems like a promising alternative to macrodomain enrichment (Leutert et al, 2017).…”
Section: Parg Treatment and Peptide Level Purification Strategy For P...mentioning
confidence: 99%